International learning experience in different cultures - Gonçalves, R.; Santana, B.; Pereira, L.; Lopes da Costa, R.; Dias, Á. (International Journal of Learning and Change, 2023)
This study aims to give an understanding about what are the main reasons that are taken in consideration by foreign students in their decision to stay or leave the country where they have completed their studies. Based on literature review a survey was built and sent to students of different nationalities, which focused on the main dimensions valued by an individual when choosing a place to live. The results showed that the variables 'perception (education)', 'environment', 'health and well-being', 'social influence', 'intention to live abroad', 'social influence' and 'intent to live abroad' where the ones with greater impact in the decision of a foreign student to stay or leave the country.